A study on the modelling for predicting worn profile of rail with multi-body dynamics and the verifying the validity - Masahiro TSUJIE; Ariku YOSHIOKA; Yuki MIZUTANI; Yoshiaki TERUMICHI (Nihon Kikai Gakkai ronbunshu, 2017)
In recent years, railway system is attracting attention in terms of energy efficiency and environment friendliness. Rail of railway is one of the most important elements in constructing railway system. Railheads are subjected to severe contact with wheels during repeated passage of vehicles. As a results of severe contact with wheels, wear of rail or rail defect have been occurred on railheads. Rail profile will be changed due to wear development. Worn profiles of rail have changed complexity in each section because the condition of wheel/rail contact has changed gradually, according to the running condition of vehicle and track geometry condition. Therefore, it is very important to predict the worn profiles of rail based on the analysis of vehicle dynamics. Previously, we constructed the prototyped model for predicting worn profiles of rail with Simpack. However, the validation of this model has not been verified. In this study, we conducted the wear experiments by use of full-scaled wheel/rail rolling contact equipment to distinct the coefficient of wear and to measure the worn profiles for validating the prediction model. Moreover, we analyzed the worn profile of rail in the same contact condition with the wear experiments. Finally, we considered the results of wear depth and the contact patch of wheel/rail discs of this equipment in analysis and experiments. As a result of the analyses and experiment, the analytical model was confirmed being valid to predict worn profile of rail.